Dominican Republic Forest Note : Opportunities for Employment, Tourism, and Energy - World Bank (World Bank, Washington, DC, 2021)
The objectives of this country forest note (CFN) are to identify and determine how to address key opportunities and challenges for sustainable forestry and forest-smart interventions in the Dominican Republic. Essential questions addressed by the CFN are the importance of forests and how the forestry sector can achieve its full potential. The responses are framed by two perspectives: the importance of forests in boosting economic development in the Dominican Republic, reducing poverty, and facilitating the sustainability of such development and the role of forestry in the context of global issues, such as greenhouse gas (GHG) emission mitigation, nationally determined contribution (NDC) objectives, global poverty reduction, and the services provided by global ecosystems.